Answer:
3x+2y+2=0
3x=-2y-2
x=-(2y+2)/3
Step-by-step explanation:
Answer: A. divided the difference of the two quantities by the sum of the two quantities.
===================================================
Explanation:
The difference of the quantities is 20-15 = 5
The sum of the quantities is 20+15 = 35
Dividing those results leads to 5/35 = 0.142857 which rounds to 0.1429
That converts to 14.29%
This is likely the path Adam took. This path is incorrect. The correct steps are shown below
---------------------
Difference = 20-15 = 5
Divide the difference over the original quantity
5/20 = 1/4 = 0.25 = 25%
We have a 25% decrease because the new quantity (15) is smaller than the old quantity (20)
----------------------
Here's another way to approach the problem
A = old value = 20
B = new value = 15
C = percent change
C = [ (B-A)/A ] * 100%
C = [ (15-20)/20 ] * 100%
C = (-5/20)*100%
C = -0.25*100%
C = -25%
The negative C value means we have a negative percent change, ie we have a percent decrease. So this is another way to get a 25% decrease.
Answer:
d. H0: melanoma mortality rate is not linearly related to latitude
Ha: melanoma mortality rate is linearly related to latitude
Step-by-step explanation:
The linear regression equation is
y=α+βx where α=intercept and β=slope.
β=slope demonstrates the change in dependent variable due to unit change in independent variable.
If the slope is zero then we can say that Y and X are not linearly related.
Thus, the hypothesis for testing significance of linear relationship two variables can be written as
Null hypothesis: The two variables are not linearly related i.e. β=0
Alternative hypothesis : The two variables are linearly related i.e. β≠0.
Thus, in the given scenario the hypothesis are
H0: melanoma mortality rate is not linearly related to latitude
Ha: melanoma mortality rate is linearly related to latitude.
Answer:
The equation would be y = 1/23x - 251/23
Step-by-step explanation:
To start, you need to locate the slope of the first equation. Since the slope is the coefficient of x, we know it to be -23. Now, the perpendicular slope is the opposite and reciprocal of that, which makes the new slope 1/23.
Now that we have this, we can use the point and the slope in point-slope form to get the equation.
y - y1 = m(x - x1)
y - 11 = 1/23(x - 2)
y - 11 = 1/23x - 2/23
y = 1/23x - 251/23
The answer is Graph, I hope it helps:)